MICROCONTROLLER ATMEGA328P TIMER/COUNTER FOR SINGLE CHANNEL GAMMA SPECTROSCOPY - Santiko Tri Sulaksono; Putu Sukmabuana; Nanda Nagara (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
Soil contamination may occur in the upcoming decommissioning activities of the TRIGA2000 Reactor. Measurement of contaminant radioactivity, which can be performed using single-channel spectroscopy, is required in soil decontamination processes. This research develops a timer/counter system for single-channel spectroscopy using a microcontroller. The performance of the ATMega328P microcontroller Timer/Counter on Arduino has been tested for single-channel spectroscopy. Microcontroller's Timer/Counter1 is used as a counter while Timer/Counter2 is used as a timer. Tests include the linearity test, comparative test, and chi-square test. The test results show that the ATMega328P microcontroller Timer/Counter works well and can be used as the end of a single-channel spectroscopic system.